Repairing Distortion-Induced Fatigue Cracks in Steel Bridge Girders Using Angles-with-Plate Retrofit Technique. II: Computer Simulations - Alemdar, Fatih; Overman, Temple; Matamoros, Adolfo; Bennett, Caroline; Rolfe, Stan (ASCE-AMER SOC CIVIL ENGINEERS, 2014)
This paper presents the results from computer simulations of 914 mm (36 in.) deep girder-cross frame subassemblies to study the effects of distortion-induced fatigue and to evaluate the effectiveness of a newly proposed cost-effective retrofit measure. The proposed retrofit measure consists of adding steel angles connecting the girder web and the transverse connection plate (CP), and a steel plate on the back side of the girder web. The retrofit measure is intended to reduce stress demand at the welds, to restrain the web-gap region from deforming in the out-of-plane direction, and to distribute lateral forces transferred by cross-frames over a wider region of the web. Parametric studies were carried out to determine the optimal configuration to prevent growth of fatigue cracks of various lengths in the web-gap region. It was found that the proposed retrofit measure reduced peak stress demands with respect to the unretrofitted configuration by 50% or more, making it likely that it will prevent fatigue crack reinitiation. The parametric studies showed that the proposed retrofit measure became more effective in reducing the peak stress demand as the stiffness of the elements increased, with the lowest average stress demand occurring when the angles and backing plate were assigned thicknesses equal to 2.67 times the thickness of the web. Experimental verification of this study is presented in a companion paper. (C) 2014 American Society of Civil Engineers.
Keywords: Fatigue; Repair; Distortion-induced fatigue; Steel; Plate-girder; Angles-with-plate; Metal and composite structures; Construction & Building Technology; Engineering